Analysis of Financial Distress, Profitability, Liquidity, Leverage on Share Prices of Manufacturing Companies Listed on the IDX - Dahlia Pinem; Marlina Tanjung; Anggi Angga Resti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine the influence of the variables Financial distress, profitability, liquidity and Leverage on Manufacturing stock returns on the IDX in 2020-2021, in the phenomenon there are differences between real data and theory as well as research gaps that exist in previous research. The sampling method uses a purposive sampling method. The analysis technique used in this research uses Eviews Panel Data Regression Analysis version 12 and a significance level of 5% and in selecting the model the Chow test, Hausman test and Lagrange Multiplier test are used, which is better. The research results show that financial distress calculated using the Taffler model has a significant influence on stock returns with a significance value of 0.0022. Meanwhile, Profitability, Liquidity, Leverage have no effect and are not significant on stock returns